Individual and age-related variation of cellular brain composition in a squamate reptile - Kverková, Kristina; Polonyiová, Alexandra; Kubička, Lukáš; Němec, Pavel (Biology letters, 2020)
Within-species variation in the number of neurons, other brain cells and their allocation to different brain parts is poorly studied. Here, we assess these numbers in a squamate reptile, the Madagascar ground gecko (Paroedura picta). We examined adults from two captive populations and three age groups within one population. Even though reptiles exhibit extensive adult neurogenesis, intrapopulation variation in the number of neurons is similar to that in mice. However, the two populations differed significantly in most measures, highlighting the fact that using only one population can underestimate within-species variation. There is a substantial increase in the number of neurons and decrease in neuronal density in adult geckos relative to hatchlings and an increase in the number of neurons in the telencephalon in fully grown adults relative to sexually mature young adults. This finding implies that adult neurogenesis does not only replace worn out but also adds new telencephalic neurons in reptiles during adulthood. This markedly contrasts with the situation in mammals, where the number of cortical neurons declines with age.
Keywords: brain size; Madagaskar; mozek; intraspecific variation; ještěři; telencefalon; cellular scaling rules; number of neurons; zvířata; neurony; myši; Mice; number of glial cells; Madagascar; Brain; Neurons; Lizards; Animals; evolution; Telencephalon